Synthetic biology of polyketide natural products: Refactoring the landomycin A biosynthetic pathway - Nieminen, Oona (My University, 2025)
Streptomyces are filamentous, spore-forming, Gram-positive bacteria found in various environments particularly in aquatic and terrestrial habitats. They are known for producing bioactive secondary metabolites, which are often referred to as natural products. These natural products have historically led to the discovery of clinically important compounds, including antibiotics, antivirals, anticancer agents and many more. The secondary metabolism of Streptomyces is complex and they produce a variety of structurally diverse compounds, hence more than two-thirds of the antibiotics used today are produced by different Streptomyces species. The research to discover novel natural products from Streptomyces is ever going to fight the rise of antibiotic-resistant bacteria and drug-resistant cancer cell lines along with finding new treatment options for diseases. One of the largest classes of natural products produced by Streptomyces are angucyclines, which are type II polyketides with a benz[a]anthracene core. Landomycins are angucyclines that have been 8-O-glycosylated with deoxysugars. Landomycin A (LaA) is the largest naturally occurring landomycin, with a hexasaccharide glycan composed of D-olivose and L-rhodinose monomers. Many landomycins have shown potential anticancer activity, with LaA possessing one of the highest cytotoxic potencies across the board. S. cyanogenus S136 harbors a large biosynthetic lan gene cluster composed of 33 genes, which is responsible for the biosynthesis of LaA. The cluster contains several regulatory genes that putatively function in a hierarchical manner, which has made production of LaA in laboratory conditions challenging. Synthetic biology aims to re-engineer biological systems to improve the manufacturing of bioproducts. In this study, the biosynthetic gene cluster of LaA was refactored using synthetic genes and transcriptional elements with BioBricks assembly standard, in order to bypass the complexities related to the production of LaA. Multiple plasmids were created containing the post-PKS tailoring enzymes, glycosyltransferases and the genes for TDP-sugar synthesis, and successfully cloned and conjugated into Streptomyces coelicolor M1152 ∆matAB. However, strains harbouring the full pathways in four plasmids displayed decreasing growth rates indicating accumulation of toxic compound. No glycosylated metabolites compounds or LaA production was observed suggesting that the toxicity issues were caused by early pathway intermediates. The results were confirmed with new gene constructs containing only one or two tailoring enzymes, which pinpointed that the toxicity issues were caused by the lanV 6-ketoreductase. The work suggests that the complex native regulatory system in S. cyanogenus S136 may be required to fine-tune gene expression in a manner that prevents self-toxicity issues.
Keywords: BioBricks, landomycin A, metabolic engineering, natural products, secondary metabolism, Streptomyces, synthetic biology